Why would you use medical chatbots? interview and survey. (September 2022) - Chang, I-Chiu; Shih, Yi-Syuan; Kuo, Kuang-Ming
Highlights: This study investigated the usage intention of medical chatbots to bridge the gap of insufficient behavioral research. A research model based on interviews and theory of planned behavior was proposed. The adapted research model can explain the variation of medical chatbots usage intention reasonably. Abstract: Background: Chatbots, empowered by artificial intelligence, are becoming increasingly popular in many fields and have much potential for application in real life situations. However, little attention has been paid to medical chatbots and most existing evidence focuses on technical issues while behavioral research is still lacking. Objective: This study seeks to examine the key factors that can motivate individuals to use medical chatbots. To that end, we have extended the theory of planned behavior by incorporating pertinent constructs derived after interviews with users. A research model and hypotheses are then proposed and tested. Methods: Interviews were first conducted to collect qualitative data from 20 participants based on purposive sampling. Content analysis was then used to find evidence supporting important constructs for a research model. A survey methodology based on convenience sampling was then used to collect data. Totally, 205 valid responses were gathered and analyzed by using partial least squares structural equation modeling to validate the research model. Results: Health consciousness and perceived convenience were found positively associated with individuals' attitudes towards the use of medical chatbots. Moreover, attitude and subjective norm were found to be significantly and positively related to individuals' intentions to use medical chatbots. Conclusions: The proposed model with the extended theory of planned behavior is able to predict individuals' intention to use medical chatbots well. Hospital managers can formulate strategies to improve individuals' health consciousness and perceptions of convenience to develop the desired attitudes among individuals, using medical chatbots. Further, strategies to improve patients' awareness of medical chatbots should also be formulated.